Brain thinking styles related to the consumer behaviour in university students - Torres Lajo, Manuel Pedro (2020)
This article has as main objective to establish the existent correlation between the Brain Thinking Styles and Consumer Behaviour in a probabilistic sample of 318 students from the economics faculty of a public university in Lima, Peru. Two instruments, with consistent levels of validity and reliability, were applied to these students: the Inventory of Brain Thinking Styles of Carlos Alberto Jiménez, and the Consumer Style Inventory of Sproles and Kendall, which the author of this article adapted for research purposes. The results show the influence that the Brain Thinking Styles have on the Consumer Behaviour in the studied sample. This is reflected in both the behaviour of the more emotional consumer and the more rational consumer. In both factors, it is possible to appreciate the effects that emotions have on consumer behaviour, because, even in rationality, the emotional areas of the brain have an influence. JEL: D91, D87, D12, M31.